Care Quality, Patient Safety, and Nurse Outcomes at Hospitals Serving Economically Disadvantaged Patients: A Case for Investment in Nursing. (February 2022) - Viscardi, Molly Kreider; French, Rachel; Brom, Heather; Lake, Eileen; Ulrich, Connie; McHugh, Matthew D.
We sought to evaluate if better work environments or staffing were associated with improvements in care quality, patient safety, and nurse outcomes across hospitals caring for different proportions of patients who are economically disadvantaged. Few actionable approaches for hospitals with quality and resource deficits exist. One solution may be to invest in the nurse work environment and staffing. This cross-sectional study utilized secondary data from 23, 629 registered nurses in 503 hospitals from a four-state survey collected in 2005–2008. Each 10% increase in the proportion of patients who are economically disadvantaged was associated with 27% and 22% decreased odds of rating unit-level care quality as excellent and giving an "A" safety grade, respectively. Each 10% increase was also associated with 9%, 25%, and 11% increased odds of job dissatisfaction, intent to leave, and burnout, respectively. The work environment had the largest association with each outcome. Accounting for the nurse work environment lessened or eliminated the negative outcomes experienced at hospitals serving high proportions of patients who are economically disadvantaged. Leaders at hospitals serving high proportions of patients who are economically disadvantaged, as well as state and federal policymakers, should work to improve quality, safety, and nurse outcomes by strengthening nurse work environments. Improving work environments highlights the role of nursing in the health care system, and policies focused on work environments are needed to improve the experiences of patients and nurses, especially at hospitals that care for many patients who are economically disadvantaged.